A comparative study of mixed-integer linear programming and genetic algorithms for solving binary problems - Kuendee, Punyisa; Janjarassuk, Udom (My University, 2018)
This paper aims to investigate the capability of mixed-integer linear programming (MILP) method and genetic algorithm (GA) to solve binary problem (BP). A comparative study on the MILP method and GA with default and tuned setting to find out an optimal solution is presented. The mixed-integer programming library (MIPLIB 2010) is used to test and evaluate algorithms. The evaluation is shown in quality of the solution and the execution time of computation. The results show that GA is superior to MILP in execution time with inconsistent results. However, MILP is superior to GA in quality of the solution with more stable results.
Keywords: binary problem; genetic algorithm; mixed integer programming library; mixed-integer linear programming